CMET-13. THE COMPOSITION OF NEWLY-DIAGNOSED BRAIN METASTASES VARIES WIDELY BY PATIENT DEMOGRAPHICS. (11th November 2019) - Kavouridis, Vasileios; Torre, Matthew; Harary, Maya; Smith, Timothy; Iorgulescu, Bryan
Abstract: INTRODUCTION: Metastases comprise a significant subset of all intracranial neoplasms, but their national composition remains unclear and challenging to track in national cancer registries. METHODS: The patient demographics and histologic distribution of newly-diagnosed brain metastasis (BM) patients aged >18yo without a prior history of cancer (2010–2015) were evaluated using the National Cancer Database, which comprises >70% of all newly-diagnosed cancers in the U.S. RESULTS: 91, 686 adults presented with a newly-diagnosed BM between 2010–2015. The most common sites of brain metastases overall were lung (82% of metastatic cases), breast (4.1%), melanoma (3.2%), kidney (2.9%), and colorectal (1.8%). The overall 1-year and 5-year OS rates for all metastatic tumors were 27.0% (95%CI=26.7–27.3]) and 5.3% (95%CI=5.1–5.5), respectively. The distribution of primary sites for newly diagnosed intracranial metastases varied by sex, age, and race. Compared to males, more females had BMs from breast (8.4% versus 0.8%) and fewer had BMs from kidney (1.9% versus 3.8%), melanoma (1.9% versus 4.5%), and esophagus (0.3% versus 2.0%). In young adults, particularly those 20-29yo, BMs were more likely from melanoma, genitourinary (in males), and soft tissue than adults in middle and advanced age. Lung carcinomas comprised fewer BMs in Hispanics (66%) compared to Whites (82%), Blacks (83%), and Asian/Pacific Islanders (85%). BMs from kidney and genitourinary primaries were higher in Hispanics (7.3% and 2.4% of BMs, respectively) than in Whites (2.8% and 0.3%, respectively), Blacks (1.8% and 0.1%, respectively), and Asian/Pacific Islanders (2.6% and 0.2%, respectively). Melanoma was more frequent in Whites (3.8% of BMs) and Hispanics (2.5%) compared to Blacks (0.3%) and Asian/Pacific Islanders (0.6%). CONCLUSION: Our results illustrate the national distribution of newly-diagnosed BMs and investigates how the distribution varies by patient demographics.